Radiobiological perspective on metrics for quantifying dose enhancement effects of High-Z nanoparticles - Luo, Yan (Frontiers in Nanotechnology, 2025)
High atomic number (high-Z) metal nanoparticles (NPs) have emerged as transformative radiosensitizers in cancer radiotherapy, offering the potential to amplify tumor-specific radiation effects while sparing healthy tissues. However, the clinical translation of these NPs is hindered by inconsistent methodologies for quantifying dose enhancement and a limited understanding of how biological complexity influences therapeutic outcomes. This review systematically evaluates current metrics for assessing high-Z NP-mediated radiosensitization, including physical dose enhancement factors (DEF), sensitizer enhancement ratios (SER), survival fraction (SF), and DNA damage biomarkers. We critically analyze the interplay between NP properties, radiation parameters, and tumor microenvironment (TME) dynamics, emphasizing how hypoxia, immune suppression, and stromal barriers modulate therapeutic efficacy. A key innovation is the proposal of a multidimensional Radiosensitization Index (RSI), integrating physical dose deposition, reactive oxygen species (ROS) kinetics, DNA repair inhibition, immune reprogramming, and clinical endpoints. We further highlight translational challenges such as NP toxicity, batch-to-batch variability, and the discordance between in vitro and in vivo models, underscoring the need for standardized protocols and advanced 3D/organoid platforms. By bridging radiobiology, nanotechnology, and clinical practice, this work provides a roadmap for optimizing NP-enhanced radiotherapy and accelerating its integration into precision oncology.